Primary Education Reform in Montenegro from the Perspective of Teachers and Parents - Mićanović, Veselin (Revija za elementarno izobraževanje, 2019)
The Montenegrin educational system at the beginning of the new millennium is characterized by intense reform efforts. The research aims to look at key aspects of the reform process in primary education in Montenegro from the perspective of its participants - teachers and parents. The qualitative research was carried out through focus group interviewing. The results show that considerable progress has been made, but they also point to serious shortcomings such as the lack of institutional support for schools in the processes of planning, teacher training and new curriculum implementation.
Keywords: Montenegro; regorm; primary education; pupil; parent; teacher